2015
DOI: 10.3109/13645706.2015.1119701
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized indication for robot-assisted cardiac surgery: Patients with acute psychotic disorders

Abstract: Patients with acute psychotic disorders are often considered as inappropriate candidates for cardiac surgery as well as for other surgical interventions. Post-operative care and patient compliance, which are the main problems associated with such patients, are the most important issues for conventional cardiac surgery. Robot-assisted cardiac surgery may be a new solution in this respect. In this report we aimed to present our acute psychotic patient with serious mitral insufficiency secondary to huge atrial my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Furthermore, sternal stability is one of the main factors for patients with postoperative agitations and delirium. Demirkilic et al reported a robotic atrial myxoma excision in a patient with psychotic disorders and concluded that robotic cardiac surgery should be considered the gold standard surgical technique in patients who are incompatible with routine postoperative care. We also believe that robotic surgery seems to be a very good option for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sternal stability is one of the main factors for patients with postoperative agitations and delirium. Demirkilic et al reported a robotic atrial myxoma excision in a patient with psychotic disorders and concluded that robotic cardiac surgery should be considered the gold standard surgical technique in patients who are incompatible with routine postoperative care. We also believe that robotic surgery seems to be a very good option for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The DaVinci™ Robotic System enables the surgeon to visualise the surgical field in detail with three‐dimensional, 10‐times magnified high‐definition visualisation and provides perfect mobility of endoscopic instruments. In addition, robotic arms have the ability to tremor‐free movements with 5400 3,5 . Therefore, more complex procedures as in our study population can simply be performed with robotic approach.…”
Section: Discussionmentioning
confidence: 99%
“…The daVinci ® SI model (Intuitive Surgical Inc.,) was used. We described our standard robotic set‐up and surgical technique in our previous papers 3–5 . Briefly, common femoral vein was used for inferior caval decompression and right jugular vein was used for superior caval decompression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations